Water quality trading: Theoretical and practical approaches - Marianne Keudel (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2006)
Permit trading as an instrument to control air pollution has already been implemented in several countries, so in Europe since 2005. Could this instrument, however, also be adequately used for water pollution control of river basins in form of a water quality trading? Specific characteristics of rivers, pollutants and pollution sources strongly influence the design of such an instrument. This paper reviews theoretical and practical approaches on water quality trading. It is surprising that these approaches have never been linked by the literature. To fill this gap, this paper gives a first idea, how different water quality trading approaches (in theory and practice) can be made comparable.
Keywords: Q53; Q25; 330; water quality trading; water pollution control; river basin management